Gamification of a Procurement Process for Professional Training of Public Servants - Maksims Kornevs; Jannicke Baalsrud Hauge; Sebastiaan Meijer (Serious Games Society, 2019)
Implementation and training about changes in a procurement process are complex due to the complexity of the procurement process characterised by the adaptive stakeholder network and continuously changing market rules. Traditional training approaches for procurement split the process into separate steps; however, to be able to assess all training aspects, it is important to have a holistic look at procurement. This work explores how well gamification can address the complexity of the procurement process for training specialists in the road construction sector. A case study is carried out to train new business models for both experienced specialists and new employees. The steps for the development of gamification for training in procurement are shown. A comparison of results from experienced and less experienced participants is presented. The results show the relationships amongst the complexity of the real system, the gamification design and the results of gamification.